Du retrait à la reconquête. Pratiquer la ville après un épisode psychotique. - Codeluppi, Zoé (Geographisch-Ethnographische Gesellschaft Zürich, 2019)
The article aims to provide a better understanding of the urban practices of young people living with a diagnosis of psychosis while recovering. It shows the way practices are adjusted according to the temporal dynamics of psychosis. It argues that the continuous variability of symptoms over the recovery period implies alternately practices of withdrawal and reconquest of the urban space. It first outlines participants' reconquest of urban spaces, which starts in well-known places and then extends to less familiar ones. In doing so, it points out the diversity of urban spaces inhabited by participants during the recovery process which includes institutional, private, as well as public places. It then outlines the various material, relational and sensory resources available in these spaces. It shows how participants use them according to the temporal dynamics. It finally highlights the way participants are gradually getting involved in the relationship with a large array of resources as the intensity of symptoms is reducing. The analysis is based on a three months ethnography in a therapeutic institution in Lausanne.
Keywords: Stadtsoziologie; Stadtbewohner; Kranker Mensch; Alltagsleben; Öffentlicher Raum; Privater Raum; Raumnutzung; Bewegungsraum; Raumaneignung; Verhalten; Bewegung; Umgebung; Empirische Untersuchung; Psychische Erkrankung; Psychisch Kranker; Ethnographie